Lily the thief - Kukkonen, Janne, 1983- (First Second, 2019)
"Lily is a young novice who dreams of being a master thief. That's not easy when the Guildmaster of Thieves only assigns you the lowliest jobs: pick-pocketing, trespassing, and petty theft. But on one of these meager quests, Lily unearths a plot involving a mysterious cult and long-forgotten gods -- a secret that could destroy the whole world. Lily must fight to save the same people who have branded her an outcast. Can she use her cunning to put an ancient evil to rest?"--